2004
DOI: 10.1007/s00024-004-2531-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Maximum Earthquake Magnitude, m max

Abstract: This paper provides a generic equation for the evaluation of the maximum earthquake magnitude m max for a given seismogenic zone or entire region. The equation is capable of generating solutions in different forms, depending on the assumptions of the statistical distribution model and/or the available information regarding past seismicity. It includes the cases (i) when earthquake magnitudes are distributed according to the doubly-truncated Gutenberg-Richter relation, (ii) when the empirical magnitude distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
204
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(212 citation statements)
references
References 69 publications
4
204
0
4
Order By: Relevance
“…McGuire (2004) and Kijko (2004). While represents the maximum magnitude of an induced seismic event during the development of a geothermal reservoir (exploration, stimulation, circulation), stands for the very rare seismic event happening only every thousand or ten thousand years, and is difficult to be estimated based on observed data (Holschneider et al, 2014).…”
Section: Maximum Observed and Expected Seismic Magnitudementioning
confidence: 99%
“…McGuire (2004) and Kijko (2004). While represents the maximum magnitude of an induced seismic event during the development of a geothermal reservoir (exploration, stimulation, circulation), stands for the very rare seismic event happening only every thousand or ten thousand years, and is difficult to be estimated based on observed data (Holschneider et al, 2014).…”
Section: Maximum Observed and Expected Seismic Magnitudementioning
confidence: 99%
“…In recent studies, we demonstrated that the absolute maximum magnitude M cannot be estimated properly from earthquake catalogs alone (Holschneider et al, 2011). On the contrary, M enters in the frequency-size distribution and must be set to some value (Pisarenko et al, 1996;Kijko, 2004) in order to allow the calculation of the seismic hazard. Although the influence of M for short-time horizons is usually limited, it cannot be neglected for longtime horizons.…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, statistical methods can be used to estimate M max (e.g., Kijko, 2004). In these approaches, the magnitude-frequency distribution of earthquakes can be assumed to follow a truncated GR distribution (Kijko, 2004;Holschneider et al, 2011).…”
Section: Usual Methodsmentioning
confidence: 99%
“…In these approaches, the magnitude-frequency distribution of earthquakes can be assumed to follow a truncated GR distribution (Kijko, 2004;Holschneider et al, 2011). It is also possible to use a magnitude-frequency distribution with no a priori prescribed analytical shape (e.g., Kijko, 2004). Other methods use the theory of extreme values of random variables (Pisarenko et al, 2008(Pisarenko et al, , 2010.…”
Section: Usual Methodsmentioning
confidence: 99%